The impact of the COVID-19 pandemic on HIV healthcare delivery for females in sub-Saharan Africa: A scoping review. - Reeya Kothari; Rachel Victoria Baran; Paulina Rudziak; Vishva Shah; Elysée Nouvet (PLOS Global Public Health)
Throughout sub-Saharan Africa (SSA), females are disproportionately impacted by HIV and face generalized but also gendered social and economic barriers to accessing HIV healthcare and services. At the outset of the pandemic, many anticipated COVID-19 would represent a major set-back for HIV care in the region. The impact of COVID-19 on HIV health services and HIV-affected populations has been reported in specific populations but has not been synthesized for females in the SSA region. The objective of this scoping review is to investigate the impact of COVID-19 on HIV healthcare delivery and services for females in SSA. Four databases were searched to identify relevant studies. Studies included were limited to English primary research articles reporting on the interactions between COVID-19 and HIV healthcare delivery and services amongst females in SSA. Two pairs of reviewers each screened 1390 articles via abstract and full-text screening, and data extraction was facilitated with a standardized protocol. A total of 39 studies were included in this review. Through thematic analysis of the articles, we identified five major themes-accessibility, availability, affordability, clinical barriers, and psychosocial barriers-which complicated the provision of HIV care during the COVID-19 pandemic and facilitators of HIV care during the pandemic. The literature highlighted two special populations, female sex workers and pregnant females, as having unique challenges in accessing HIV care due to societal stigma and their personalized health needs. Reviewed articles indicate that the COVID-19 pandemic introduced and exacerbated barriers to the accessibility, availability, and affordability of HIV healthcare and services for females in SSA. This review should be used by healthcare workers, healthcare administrators, policymakers, and the government to better understand the current gaps in HIV service provision to females during the COVID-19 pandemic, which can support the delivery of HIV care to females for future public health emergencies.